PENINGKATAN KEEFEKTIFAN PEMBELAJARAN MENULIS DI KELAS II SEKOLAH DASAR - Suyatinah Suyatinah (Jurnal Cakrawala Pendidikan, 2005)
AbstractThis article is based on a research study aimed at finding out the effectiveness of the teaching-learning process of writing in the 2nd grade of the state elementary school.The study was a classroom action research and the subjects were the teachers and students of the 2nd grade of the State Elementary School of Ngaglik, Sardonoharjo. The research consisted of three cycles. The study involved the teachers and the principal, who were concerned with improvements in the effectiveness of the teaching-learning process in the 2nd grade of the state elementary school. All of them were involved in (1) the discussion and unification of ideas concerning the effectivenessof the teaching-learning process in the 2nd grade to identify and formulate the research problem, (2) the planning of the actions, (3) the implementation of the actions, (4) the observation of the implementation,(5) the reflections on the results of the implementation, (6) the revision of the actions and evaluation of their implementation, and (7) the drawing of conclusions concerning the results.The results of the research were as follows: (1) the process approach and drawings as media could improve (a) students writing skill, (b) their learning motivation, and (c) their attention; (2) students activities in the State Elementary School of Ngaglik, Sardonoharjo, improved after the implementation of the actions, (3) the teachers were able to construct the design of action research on the teaching-learning process of writing using the process approach and drawings as media; and (4) the school principal, teachers, and students responded to the implementation of the teaching-learning process using the process approach and drawings as media positively.Key words: the writing skill, the process approach, drawings as media